The value added tax, with reference to South Africa - Thomson, Trevor Glenn (School of Economics, 2016)
There has been a growing interest in recent years in the Value Added Tax (hereinafter referred to as the VAT). Interest in tax reform is perennial but the factor which has generated such wide interest in the VAT has been its adoption by the member countries of the European Economic Community (EEC). The recent entry of Britain into the EEC and her adoption of the VAT have increased South African interest 1n the system because of the strong trading ties between our two countries. The Franzsen commission on taxation in South Africa gave some attention to VAT but in their own opinion not enough. This is clear from their statement: "The Commission is aware of the fact that a transition from the selective sales tax which rests on a commodity basis to a Value Added Tax, which is essentially a turnover tax, implies important administrative changes. It is felt, nevertheless, that the Value Added Tax merits further study". This thesis hopes to satisfy some of that need for further study. The aim of the thesis is not to arrive at a definite conclusion as to whether South Africa should or should not adopt the VAT, indeed, it may be impossible to answer this question completely objectively. Rather the thesis sets out to examine the implications, both theoretical and practical, of a VAT, and to present certain guide-lines as to what may constitute the best form of a VAT should it be decided to introduce this mode of taxation. There is no separate section on South Africa. Instead, the implications for South Africa have been integrated into the main body of the text. For this reason, the emphasis throughout has been on the VAT replacing the selective sales tax and, to a lesser extent, the profits tax. It is felt that the selective sales tax would be the tax most likely to be replaced by the VAT in South Africa, and that the added revenue which could be collected from the broader-based VAT could possibly be off-set against the revenue lost on a reduction in company profits tax. Such a measure would certainly be well received among business men.